Effect of 20 minutes 3-prism base-out wear on accommodation parameters - Abdul Halim, Raihanah Athirah; Othman, Shah Farez; Ithnin, Mohd. Hafidz; Tamchek, Nizam (CEDEC Training Sdn. Bhd., 2025)
Accommodation involves changes in lens shape and optical power facilitated by the ciliary muscle, while vergence adjusts binocular gaze for different distances. Prism, used in treating binocular vision issues, induces convergence and thereby affects accommodation indirectly, especially during near tasks. Spectacle wearers may inadvertently experience prism effects due to optical centre misalignment, potentially impacting accommodation. Previous research combining prism-induced effects on vergence and accommodation among individuals with normal binocular vision found no significant effects, although the specific impact on accommodation remains underexplored. This study aims to provide focused insights into the specific effects of prism-induced accommodation, addressing gaps left by previous research. The purpose of this research was to compare the accommodation parameters before and after 20 minutes of 3-prism base-out wear. Thirty (30) subjects were recruited in this clinical cross-sectional study and all subjects wore the 3-prism base-out for 20 minutes while watching a movie at 6 m distance. All accommodation parameters were measured before and after watching the movie at 6 m with 3-prism base-out inducement. The results showed that there was no significant difference in accommodation parameters before and after the intervention except for the monocular accommodation facility, which were on the right eye (p=0.001) and left eye (p=0.007). In conclusion, it was suggested that wearing 3-prism base-out during distance fixation for 20 minutes had increased monocular accommodation facility in healthy individuals. This indicates that this approach may potentially benefit patients with accommodative infacility, suggesting further exploration for alternative treatments